Indicador de fragilidade financeira externa : uma análise para o Brasil pós-1995 - Xavier, Douglas Henrique de Souza (2017)
This dissertation is an effort to expand Minsky's Financial Instability Hypothesis (1986) for open economies in order to investigate the external financial fragility which Brazil was subjected in the post-1995 period. For that, the External Financial Fragility Indicator (IFFE) was constructed based on the balance of payments’ financial and real flows, with the object analyze the composition – and hence the stability – of the flows of foreign exchange entering and leaving the country (and for the countries in general, since it is based on BPM6 of the International Monetary Fund, the IFFE has wide application). Alternatively, by making it possible to infer the position of the international real and financial flows, the IFFE allows us to conclude the sustainability (that is, the greater or lesser financial fragility, of the country's foreign exchange availability) to comply with foreign currency commitments, with the classification of the behavior of the external sector in relation to the financial postures pointed out in the Minsky’s theory, using the parameters elaborated in this dissertation. The results of the application of the IFFE to Brazil in the analyzed period indicated that the country's stock of international reserves, which was increasing in the investigated period was composed mainly by currencies from the financial account, considering current account deficits also showed a growth trend in the period (there were only surpluses in the period from 2003 to 2007), making external financing of transactions with the rest of the world imperative. Besides the predominance of the Speculative posture in the analyzed quarters showed that the stock of reserves relies in an expressive way with more volatile resources, which implies a greater level of external financial fragility and dependence in relation to these capitals, seeing that eventual sudden movement s of them, in response to episodes of instability in the financial markets, can quickly consume this stock.